DSP and DPP are dispensable for initiation of dentin and enamel mineralization but critical for circumpulpal dentin mineralization - Tian Liang; Charles E. Smith; Yuanyuan Hu; Hong Zhang; Chuhua Zhang; James P. Simmer; Jan C.-C. Hu (Scientific Reports)
Abstract Dentin sialophosprotein (DSPP) is cleaved into the N-terminal dentin sialoprotein (DSP) proteoglycan and the C-terminal dentin phosphoprotein (DPP; the most acidic proteins in humans). To define the functions of DSP and DPP, we generated a Dspp −DPP mouse model using CRISPR/Cas9 technology and compared tooth mineralization in Dspp −DPP and Dspp −/− mice in the C57BL/6 background. In both mice, the initiation of dentin mineralization was associated with matrix vesicles. Odontoblasts appeared normal with odontoblastic processes. In Dspp −/− mice, limited mineralized dentin was observed. In Dspp −DPP/−DPP mice, dentin globules (calcospherites) with varied mineral density and unmineralized interglobular dentin were observed throughout the circumpulpal dentin. The area of predentin was smaller compared to Dspp −/− mice, but larger than wild-type mice. In Dspp −/− and Dspp −DPP/−DPP mice, enamel formation was comparable to wild-type. In both mice, Dmp1 expression in differentiating and differentiated odontoblasts was altered. We propose a model for dentin mineralization in which DSP, enriched in the peritubular dentin, propagates mineralization within the hypomineralized calcospherites in the intertubular dentin while DPP is essential for the maturation of calcospherite mineralization in the circumpulpal dentin. We conclude that DSP and DPP are dispensable for the initiation of dentin and enamel mineralization, but critical for circumpulpal dentin mineralization.